Rheb1-Deficient Neutrophils Promote Hematopoietic Stem/Progenitor Cell Proliferation via Mesenchymal Stem Cells - Gao, Juan; Hou, Shuaibing; Yuan, Shengnan; Wang, Yuxia; Gao, Yanan; Sun, Xiaolu; Wang, Weili; Chu, Yajing; Zhou, Yuan; Feng, Xiaoming; Luo, Hongbo R.; Cheng, Tao; et al. (Frontiers in Cell and Developmental Biology, 2021)
Myeloid cells have been identified as hematopoietic stem cell (HSC)-regulating cells. However, the mechanisms by which myeloid cells regulate the function of HSCs are not fully defined. Our previous study indicated that the HSCs are over-expanded in Vav1-Cre;Rheb1fl/fl mice. Here, using in vivo and in vitro models, we found that Rheb1-deficient neutrophils remodeled the bone marrow environment and induced expansion of HSCs in vivo. Further studies showed that loss of Rheb1 impaired neutrophils’ ability to secrete IL-6, led mesenchymal stem cells (MSCs) to produce more SCF, and promote HSC proliferation. We further found that IL-6 suppressed SCF mRNA expression in human MSCs. Interesting, the high level of IL-6 was also related with poor survival of chronic myeloid leukemia (CML) patients, and higher expression of IL-6 in CML cells is associated with the lower expression of SCF in MSCs in patients. Our studies suggested that blocking IL-6 signaling pathway might stimulate MSCs to secrete more SCF, and to support hematopoietic stem/progenitor cells proliferation.